2017
DOI: 10.1037/dev0000298
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating age differences in children’s and adults’ suggestibility and memory conformity effects.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractWe examined whether typical developmental trends in suggestion-induced false memories (i.e., age-related decrease) could be changed. Using theoretical principles from the spontaneous false memory field, we adapted two often-used false memory procedures: misinformation (Experiment 1) and memory conformity (Experiment 2). In Experiment 1, 7/9-year old children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(95 reference statements)
2
11
0
1
Order By: Relevance
“…In such a design, all participant witnesses are tested initially, but retrieval-enhanced suggestibility is assessed by comparing the misinformation recall probabilities between items that were included in the initial test with items that were omitted from the initial test. Our finding of the second experiment might be seen as encouraging in terms of practical issues; that is, for misinformation that is encountered after a delay, and not immediately, after someone is interviewed, retrieval may not increase suggestibility Otgaar, Howe, Brackmann, & van Helvoort, 2017;Otgaar, de Ruiter, et al, 2017). This finding is consistent with the prediction emerging from the memory reconsolidation framework, which has been applied as a secondary explanation for retrieval-enhanced suggestibility (Chan & LaPaglia, 2013;Chan et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In such a design, all participant witnesses are tested initially, but retrieval-enhanced suggestibility is assessed by comparing the misinformation recall probabilities between items that were included in the initial test with items that were omitted from the initial test. Our finding of the second experiment might be seen as encouraging in terms of practical issues; that is, for misinformation that is encountered after a delay, and not immediately, after someone is interviewed, retrieval may not increase suggestibility Otgaar, Howe, Brackmann, & van Helvoort, 2017;Otgaar, de Ruiter, et al, 2017). This finding is consistent with the prediction emerging from the memory reconsolidation framework, which has been applied as a secondary explanation for retrieval-enhanced suggestibility (Chan & LaPaglia, 2013;Chan et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…This is in contrast with a plethora of research demonstrating that younger children are more vulnerable to external suggestions than older children (e.g., Ceci & Bruck, ; Loftus, ; Otgaar, Candel, Smeets, & Merckelbach, ; Sutherland & Hayne, ). However, this result is in line with recent research showing that under certain conditions, susceptibility to suggestion increases with age (Otgaar, Howe, et al., ). This research shows that such reversals in suggestibility take place when external suggestive pressure captures the underlying meaning/associative structure of the event.…”
Section: Discussionmentioning
confidence: 97%
“…Collectively, these results suggest that false memories, regardless of whether they are simply suggested or induced using the DRM paradigm, follow an age-related increase from childhood through to adulthood because of increases in the speed and automaticity of associative activation (also see, Otgaar, Howe, Brackmann, & van Helvoort, 2017).…”
Section: Associative Activation and Development Of False Memory Creatmentioning
confidence: 83%
“…Furthermore, misinformation from familiar people such as a friend or a romantic partner has been shown to be more likely to be accepted than misinformation from a stranger (Hope, Ost, Gabbert, Healey, & Lenton, 2008). Recent research has revealed that memory conformity is apparent in both children and adults (e.g., Otgaar, Howe, Brackmann, & van Helvoort, 2017).…”
Section: Misinformation From Co-witnessesmentioning
confidence: 99%